MAKNA FENOMENA KEMATIAN MASSAL DI TENGAH PANDEMI COVID-19 BERDASARKAN REFLEKSI DARI AYUB 1: 1-22 - Eugenius Ervan Sardono; Nikodemus Hermiawan; Oktavianus Klido Wekin (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2020)
The phenomenon of mass death that occurred amid the Covid-19 pandemic made people reflect on death's meaning. Job 1: 1-22 contained a reflection on death when Job lost all of his children simultaneously to death. This research's main objective is to find the meaning of the phenomenon of mass death amid a pandemic based on the book Job 1: 1-22. The method used is qualitative, with a phenomenological and hermeneutic approach. This study found the meaning of mass death amid the Covid-19 pandemic based on Job 1: 1-22 is 1). the form of God's power, which must be recognized and accepted by humans; 2). the test of faith that God allows to occur in human life.